In-Depth Review of Loeffler Endocarditis: What Have We Learned? - Su S; Liang L; Lü L; Li M; Zhang X; Jin Y; Wei W; Wan Z (Dove Medical Press, 2024)
Shitong Su,1,2 Lianjing Liang,1 Lin Lü,1 Mingfeng Li,3 Xiaoling Zhang,4 Yongmei Jin,5 Wei Wei,1 Zhi Wan6 1Department of Emergency Medicine, West China Hospital, Sichuan University, Chengdu, 610041, People's Republic of China; 2Division of Head & Neck Tumor Multimodality Treatment, Cancer Center, West China Hospital, Sichuan University, Chengdu, 610041, People's Republic of China; 3Department of Pathology, West China Hospital, Sichuan University, Chengdu, 610041, People's Republic of China; 4Department of Cardiology, West China Hospital, Sichuan University, Chengdu, 610041, People's Republic of China; 5Department of Laboratory Medicine, West China Hospital, Sichuan University, Chengdu, 610041, People's Republic of China; 6Rare Diseases Center, West China Hospital, Sichuan University, Chengdu, 610041, People's Republic of ChinaCorrespondence: Wei Wei, Chest Pain center, Department of Emergency Medicine, West China Hospital, Sichuan University, No. 37, Guoxue Lane, Wuhou District, Chengdu, 610041, People's Republic of China, Email ww8075@126.com Zhi Wan, Rare Diseases Center, West China Hospital, Sichuan University, No. 37, Guoxue Lane, Wuhou District, Chengdu, 610041, People's Republic of China, Email 456wz@163.comAbstract: Loeffler endocarditis, eosinophilic endocarditis or eosinophilic endomyocardial disease are conditions associated with hypereosinophilia and they affect the heart function. Loeffler endocarditis is a rare endomyocardial disorder thought to be caused by eosinophilic damage. The disorder is characterized by inflammatory infiltration, formation of thrombus within cardiovascular system, and ultimately fibrosis of the afflicted area. It can lead to multiple severe complications, including thromboembolic disease, thickening of fibrous tissue in the endocardium of ventricles, valve involvement, apical obliteration, and various heart disorders. Although early clinical intervention can lead to remission, the underlying mechanisms of the disorder remain unresolved. In the present article, we summarise the existing literature concerning Loeffler endocarditis based on PubMed, Web of Science, and other medical databases to conduct an in-depth review of the epidemiology, etiology, pathophysiological mechanisms, staging, diagnosis, treatment and prognosis of Loeffler endocarditis. Meanwhile, we provide novel patients data and clinical figures of Loeffler endocarditis to supplement the understanding of this cardiac disorder. The findings presented in this article provide a basis for further studies and can be used to improve management of the disorder.Keywords: Loeffler endocarditis, hypereosinophilia, eosinophils damage